Phabongkha and the Yoginī: the Life, patronage and devotion of the Lhasa aristocrat, Lady Lhalu Lhacham Yangdzom Tsering - Repo, Joona (Journal of the Oxford Centre for Buddhist Studies, 2015)
Phabongkha Dechen Nyingpo (pha bong kha bde chen snying po, 1878-1941) was one of the most popular and influential Gelug religious figures in the Lhasa Valley during the first half of the twentieth-century. His students included not only lay people and monks from all of the most important religious institutions in the region, but also an impressive array of some of the highest-ranking aristocrats and government officials of the day. This article is focused on the life of one of Phabongkha's most important aristocratic students, Lhalu Lhacham Yangdzom Tsering (g.yang ‘dzom tshe ring, 1880-1963) and her relationship to her teacher and his lineage teachings. The development of her devotion to Phabongkha, and her and her family's sponsorship of the sustenance and popularization of his lineage in general will be considered with an aim of giving us a wider understanding of Phabongkha and his "movement". The Lhacham's devotion to the controversial protector deity Dorje Shugden (rdo rje shugs ldan), whose practice she received from Phabongkha, will also be discussed in detail, especially with regard to a number of tragedies which befell her, and which were portrayed by the later lineage as being the results of the wrathful activity of this deity.